Parasitoid of the Citrus Leafminer, Semielacher petiolatus (Girault) (Insecta: Hymenoptera: Eulophidae) - Marjorie A. Hoy; Lucia Zappala; Ru Nguyen (EDIS, 2005)
The citrus leafminer, Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae), was first detected in Florida in 1993 (Heppner 1993). This invasive pest spread rapidly throughout the citrus-growing areas and is now well established in Florida. The parasitoid Semielacher petiolatus (Girault) (Hymenoptera: Eulophdae) was introduced during July 2003 into quarantine facilities in the Division of Plant Industry in Gainesville and the Department of Entomology and Nematology in Gainesville, where it is being evaluated for possible release into Florida's citrus to augment the role of the citrus leafminer's other natural enemies. This document is EENY-313, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2003.